(untitled) (Psikologiya Journal, 2025)
Digital fan culture has fundamentally transformed the relationship between fans and idols through the formation of intense emotional attachment mediated by platform technologies and parasocial interactions. This study aims to explore how emotional attachment to idols is constructed within digital fan culture and to examine its behavioral implications across social, psychological, and economic domains. Using a qualitative interpretative phenomenological approach, in-depth interviews were conducted with active fans aged 18–30 involved in digital fandom communities. Data were analyzed through thematic analysis to identify patterns of emotional experience, parasocial dynamics, and psychological adaptation mechanisms. The findings reveal that emotional attachment emerges from layered interactions between cognitive, affective, and social processes, reinforced by platform algorithms and community dynamics. This attachment produces ambivalent behavioral outcomes, including enhanced sense of belonging, social cohesion, and prosocial behavior, alongside risks of emotional dependency, psychological distress, and social dysfunction when attachment becomes excessive. The study underscores the importance of emotional literacy, social regulation, and ethical digital frameworks in fostering a healthy and sustainable fan culture.